1, 4-butanediol dehydrogenation catalyst as well as synthesis method and application thereof

By using biological templates in the co-precipitation reaction to control the distribution of active metals, the problems of Cu agglomeration and sintering were solved, and a 1,4-butanediol dehydrogenation catalyst with high conversion, selectivity and stability was prepared.

CN119869533APending Publication Date: 2025-04-25CHINA PETROLEUM & CHEMICAL CORP +1

Patent Information

Application Number
CN202311358622.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-10-19
Publication Date
2025-04-25

AI Technical Summary

Technical Problem

The existing 1,4-butanediol dehydrogenation catalysts are prone to Cu agglomeration and sintering in the presence of high temperatures and hydrogen, resulting in problems such as decreasing catalyst production capacity, rapid inactivation and carbon deposits, affecting activity and selectivity.

Method used

The co-precipitation reaction is carried out in the presence of biological templates to accurately control the distribution of active metals, prevent the agglomeration, embedding and sintering of Cu. The catalyst precursor with uniform distribution of copper, zinc and aluminum salts and the biological template are prepared by co-precipitation reaction of copper, zinc and aluminum hydrotalcite.

Benefits of technology

Under mild reaction conditions, the catalyst has high conversion, selectivity and excellent catalytic stability, which extends the service life of the catalyst and improves the quality of the product.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119869533A_ABST
    Figure CN119869533A_ABST
Patent Text Reader

Abstract

The invention discloses a 1, 4-butanediol dehydrogenation catalyst precursor, a catalyst as well as a synthesis method and application of the 1, 4-butanediol dehydrogenation catalyst precursor. The precursor comprises a biological template and Cu / Zn / Al hydrotalcite, and the synthesis method comprises the following steps: (1) preparing a copper salt solution, a zinc salt solution and an aluminum salt solution, then uniformly mixing with the biological template, and controlling the concentration of the biological template in the obtained mixture; (2) adding the mixture obtained in the step (1) and a precipitant solution in a parallel flow manner by adopting an acid-base co-precipitation process, and aging, filtering, washing and drying after the reaction is finished to obtain a catalyst precursor; the catalyst prepared by roasting the precursor is used for preparing gamma-butyrolactone through dehydrogenation of 1, 4-butanediol, and has relatively high conversion rate, selectivity and excellent catalytic stability under mild reaction conditions.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of catalysts and relates to a 1,4-butanediol dehydrogenation catalyst and a synthesis method and application thereof. Background Art

[0002] γ-Butyrolactone (GBL) is a fine chemical product and a widely used chemical intermediate in the fields of petrochemical, pharmaceutical, textile, fragrance and pesticide. It can be used as an excellent high-boiling point extractant and absorbent. In the petrochemical industry, γ-butyrolactone is an ideal antioxidant, plasticizer, dispersant, color fixative, coagulant, etc.; in the pharmaceutical industry, γ-butyrolactone can be used as an anesthetic and sedative, etc. γ-butyrolactone can be decomposed in hot alkali solution, has good reaction performance, and can undergo a series of ring-opening and non-ring-opening chemical reactions. It is an important raw material for the synthesis of pyrrolidone and cyclopropylamine compounds.

[0003] There are different process technology routes for industrial production of γ-butyrolactone (GBL). According to the classification of synthetic raw materials, there are mainly three methods: furfural method, maleic anhydride hydrogenation method and 1,4-butanediol (BDO) dehydrogenation method. The furfural method has a complex process and high cost, and has lost its market competitiveness. At present, this method has been eliminated. The raw materials of maleic anhydride hydrogenation method are easy to obtain and the cost is low, but the acidity of the crude product is relatively high, which has a certain impact on the separation of the product and the quality of the final product. The by-products of the 1,4-butanediol dehydrogenation method are mainly tetrahydrofuran and a small amount of butanol. The components are simple and the products are easy to separate. While reducing the production cost, it also meets the quality requirements of battery electrolytes and pharmaceutical raw materials for γ-butyrolactone.

[0004] At present, the main catalyst for the dehydrogenation of 1,4-butanediol is Cu-based catalyst. CN110773174B discloses a catalyst for gas phase dehydrogenation of 1,4-butanediol to prepare γ-butyrolactone, which is composed of: Mg (6-x-y) Cu x Zn y Al2O9, wherein x=0.2-2, y=0.2-2.8. The catalyst is obtained by a coprecipitation method, firstly preparing a precursor with a hydrotalcite structure, and then calcining to obtain a finished catalyst product.

[0005] CN103044367B discloses a method for producing γ-butyrolactone by dehydrogenation of 1,4-butanediol. The catalyst used is composed of 37-52% CuO, 40-55% ZnO, 7-9.5% Al2O3 and a suitable proportion of auxiliary agents K and / or Li, wherein the CuO-ZnO-Al2O3 parent catalyst is prepared by a conventional coprecipitation method, and then the catalyst is prepared by an impregnation method.

[0006] CN103877981B discloses a catalyst for preparing γ-butyrolactone by atmospheric pressure gas phase dehydrogenation of 1,4-butanediol and a preparation method thereof. The catalyst is composed of 30-60% CuO, 15-50% ZnO, 5-25% Al2O3 and 10-30% SiO2, and is prepared by a coprecipitation method, and then polyethylene glycol and silica sol emulsion are added thereto as auxiliary agents.

[0007] Although some progress has been made in the research of Cu-based catalysts for the gas phase dehydrogenation of 1,4-butanediol to prepare γ-butyrolactone, the synthesis of catalysts is usually carried out by coprecipitation. However, it is difficult to control the morphology of the product and the distribution of active metals during the precipitation process. Some synthesis methods use the catalyst obtained by coprecipitation as the matrix, and then add other components by impregnation or direct mixing with additives. Although the doping of additives improves the skeleton structure and pore structure of the catalyst to a certain extent, it is easy to cause the active metals to agglomerate or be buried, resulting in insufficient exposure of active sites. Under the high temperature and hydrogen conditions of the reaction conditions, the above problems may lead to the agglomeration and sintering of Cu, resulting in a series of problems such as reduced catalyst production capacity, rapid deactivation and catalyst carbon deposition, affecting the activity and selectivity of the catalyst. Summary of the invention

[0008] In view of the shortcomings of the prior art, the present invention provides a catalyst precursor, a catalyst and a synthesis method and application thereof for preparing γ-butyrolactone by dehydrogenation of 1,4-butanediol. The catalyst is used for preparing γ-butyrolactone by dehydrogenation of 1,4-butanediol and can have a high conversion rate, selectivity and excellent catalytic stability under mild reaction conditions.

[0009] The inventors have found through research that the current Cu-based catalysts used for the dehydrogenation of 1,4-butanediol to prepare γ-butyrolactone are usually prepared by coprecipitation. During the precipitation process, it is difficult to control the product morphology and the distribution of active metals, which in turn affects the activity, selectivity and stability of the catalyst. The inventors have further found that by carrying out the coprecipitation reaction in the presence of a biological template, the distribution of active metals can be precisely controlled, and the agglomeration, embedding and sintering of Cu can be prevented, thereby improving the conversion rate, selectivity and stability of the catalyst.

[0010] The first aspect of the present invention provides a 1,4-butanediol dehydrogenation catalyst precursor, comprising a biological template and Cu / Zn / Al hydrotalcite.

[0011] Furthermore, the precursor is a microsphere structure.

[0012] Furthermore, the biological template is selected from one or more of lotus pollen, sunflower pollen, rapeseed pollen, lotus pollen, and camellia pollen.

[0013] Furthermore, the particle size of the precursor is 20 to 50 μm.

[0014] Furthermore, in the precursor, Cu / Zn / Al hydrotalcite particles are evenly distributed on the surface of the biological template, and the particle size is 50 to 500 nm.

[0015] Furthermore, in the precursor, the mass ratio of Cu / Zn / Al in the Cu / Zn / Al hydrotalcite is (30-60):(30-60):(5-40).

[0016] The second aspect of the present invention provides a method for synthesizing the above catalyst precursor, comprising:

[0017] (1) preparing copper salt, zinc salt and aluminum salt solutions, and then mixing them with the biological template, wherein the concentration of the biological template in the obtained mixture is controlled to be 0.01 to 0.5 g / mL;

[0018] (2) Acid-base co-precipitation process is adopted to add the mixture obtained in step (1) and the precipitant solution in parallel, and after the reaction is completed, the mixture is aged, filtered, washed and dried to obtain a catalyst precursor.

[0019] Furthermore, in step (1), the biological template is selected from one or more of lotus pollen, sunflower pollen, rapeseed pollen, lotus pollen, and camellia pollen. The particle size of the biological template is 20 to 50 μm.

[0020] Furthermore, preferably, the biological template may be pretreated before step (1). The pretreatment may be an ultrasonic treatment in the presence of a solvent, followed by drying. The treatment conditions are as follows: temperature 25-70°C, time 0.5-5.0h. The solvent is one or more of deionized water, low-carbon alcohol (low-carbon alcohol is selected from alcohols with a carbon number of 6 or less, preferably ethanol), and N,N-dimethylformamide, and the number of ultrasonic treatments is 3-6 times. The drying conditions are as follows: drying temperature is 25-80°C, and drying time is 6-24h.

[0021] Furthermore, in step (1), the copper salt, zinc salt and aluminum salt may be conventional soluble metal salts, such as at least one of nitrates, sulfates and acetates. The solvent used in the metal salt solution is at least one of water, methanol, ethanol, N,N-dimethylformamide (DMF) and the like. In the copper salt, zinc salt and aluminum salt solution, the total concentration of copper, zinc and aluminum ions is 0.5 to 5.0 mol / L.

[0022] Furthermore, in step (1), the molar ratio of the copper salt calculated as copper, the zinc salt calculated as zinc, and the aluminum salt calculated as aluminum is (0.5-2.0):(0.5-2.0):(0.1-1.0).

[0023] Furthermore, the precipitant used in the precipitant solution in step (2) is selected from one or more of sodium carbonate, sodium hydroxide, sodium bicarbonate and ammonia water. The concentration of the precipitant solution is 0.5 to 5.0 mol / L. The solvent used in the precipitant solution is selected from one or more of methanol, ethanol, water and N,N-dimethylformamide (DMF).

[0024] Furthermore, in step (2), the reaction conditions are: reacting at 25-80° C. for 0.5-5 hours, and controlling the reaction pH value to 6.0-9.0.

[0025] Furthermore, in step (2), the aging conditions are as follows: aging temperature is 25-80° C., aging time is 0.5-5 h, and pH value is 6.0-9.0.

[0026] Furthermore, in step (2), the washing solvent used in the washing is one or more of deionized water, methanol, ethanol, and N,N-dimethylformamide, and the washing times are 3 to 6 times. The drying conditions are as follows: the drying temperature is 25 to 80° C., and the drying time is 6 to 24 hours.

[0027] The third aspect of the present invention provides a 1,4-butanediol dehydrogenation catalyst, wherein the catalyst is obtained by calcining the above catalyst precursor.

[0028] Furthermore, in the catalyst, the weight content of each component is as follows: CuO 30% to 60%, ZnO 30% to 50%, Al2O3 5% to 20%.

[0029] Furthermore, the microstructure of the catalyst is a microspherical structure.

[0030] Furthermore, the specific surface area of ​​the catalyst is 40 to 150 m 2 / g, pore volume is 0.20~0.65m 3 / g, and the average pore size is 20-28nm.

[0031] Furthermore, the calcination conditions are as follows: the heating rate to the calcination temperature is 4-8°C / min, the calcination temperature is 300-500°C, the calcination time is 2-6h, and the calcination atmosphere is an oxygen-containing atmosphere, such as air.

[0032] The fourth aspect of the present invention provides a method for preparing the above catalyst, comprising: calcining the above catalyst precursor to obtain the catalyst.

[0033] Furthermore, in step (4), the calcination conditions are as follows: the heating rate to the calcination temperature is 4-8°C / min, the calcination temperature is 300-500°C, the calcination time is 2-6h, and the calcination atmosphere is an oxygen-containing atmosphere, such as air.

[0034] Furthermore, the catalyst can be a shaped catalyst, and the forming method is tableting, that is, adding 1% to 5% of the mass of the calcined material with graphite powder, and screening out catalyst particles of 20 to 40 mesh to obtain the shaped catalyst.

[0035] The fifth aspect of the present invention provides the use of the above catalyst in the dehydrogenation of 1,4-butanediol to synthesize γ-butyrolactone.

[0036] Furthermore, the catalyst needs to be reduced before the reaction. The preferred reducing atmosphere is hydrogen. The reducing conditions are as follows: hydrogen pressure is 0 to 0.5 MPa, reduction temperature is 150 to 300° C., and reduction time is 6 to 24 h.

[0037] Furthermore, the application includes: in the presence of hydrogen, 1,4-butanediol is contacted with the catalyst to react and produce γ-butyrolactone.

[0038] Further, the reaction conditions are as follows: the reaction temperature is 150-300°C, preferably 215-230°C, the reaction pressure is 0.1-1.0 MPa, preferably 0.1-0.5 MPa, and the volume space velocity is 0.1-2.0 h -1 , preferably 0.3 to 1.5h -1 The molar ratio of hydrogen to 1,4-butanediol is 1 to 150:1, preferably 1 to 30:1.

[0039] Compared with the prior art, the present invention has the following advantages:

[0040] 1. The catalyst of the present invention is used for dehydrogenation of 1,4-butanediol to prepare γ-butyrolactone, and can have high conversion rate, selectivity and excellent catalytic stability under mild reaction conditions;

[0041] 2. The catalyst precursor of the present invention is obtained by co-current precipitation reaction of a mixture of copper, zinc and aluminum salts and a biological template with a precipitant solution. The biological template provides active sites for the growth and nucleation of the precursor. The copper-zinc-aluminum hydrotalcite obtained by the reaction is evenly distributed on the surface of the biological template, thereby achieving precise control of the distribution of active metals and preventing the agglomeration, embedding and sintering of Cu. It is used for the dehydrogenation of 1,4-butanediol to prepare γ-butyrolactone, and can have high conversion rate, selectivity and excellent catalytic stability under mild reaction conditions;

[0042] 3. The bio-template used in the catalyst preparation method of the present invention can be removed through the calcination process, and no subsequent treatment steps such as acid and alkali are required. The preparation process is simple and suitable for industrial production. BRIEF DESCRIPTION OF THE DRAWINGS

[0043] Figure 1X-ray diffraction (XRD) diagrams of the catalyst A1 precursor and the unformed catalyst A1 of Example 1;

[0044] Figure 2 This is a SEM image of the catalyst A1 precursor of Example 1;

[0045] Figure 3 This is a SEM image of the unformed catalyst A1 synthesized in Example 1;

[0046] Figure 4 This is a SEM image of the unformed catalyst A2 synthesized in Example 2;

[0047] Figure 5 This is a SEM image of the unformed catalyst A3 synthesized in Example 3;

[0048] Figure 6 This is the SEM image of the unformed catalyst B1 synthesized in Comparative Example 1;

[0049] Figure 7 This is the SEM image of the unformed catalyst B2 synthesized in Comparative Example 2. DETAILED DESCRIPTION

[0050] The present invention will be further described below in conjunction with embodiments, but it should be understood that the protection scope of the present invention is not limited by the embodiments.

[0051] Example 1

[0052] This example provides a method for preparing a catalyst for synthesizing γ-butyrolactone by dehydrogenation of 1,4-butanediol, as follows:

[0053] (1) copper nitrate, zinc nitrate and aluminum nitrate were prepared according to the mass ratio of copper: zinc: aluminum of 45:45:10, and the concentration of the metal salt solution was 2.0 mol / L, and lotus powder (particle size of 20-50 μm) was added thereto, and the concentration of the bio-template in the obtained mixture was controlled to be 0.1 g / mL;

[0054] (2) The precipitant solution is a sodium bicarbonate aqueous solution, and the concentration of the precipitant solution is 1.0 mol / L; the acid-base co-precipitation process is adopted, and the mixture obtained in step (1) and the precipitant solution are added in parallel, and the reaction temperature is controlled at 60°C, the reaction pH value is 7.0, and the reaction time is 2h. After the reaction is completed, it is aged at 70°C for 2h, filtered and separated, and washed with deionized water for 6 times, and dried in an oven at 60°C for 12h. The catalyst precursor is collected and its XRD pattern is as follows Figure 1 As shown by Figure 1 It can be seen that the catalyst precursor is a copper-zinc-aluminum hydrotalcite structure. Figure 2 ,Depend on Figure 2It can be seen that the precursor is a microsphere structure with a particle size of 20 to 50 μm, and the copper-zinc-aluminum hydrotalcite is evenly distributed on the surface of the biological template with a particle size of 100 to 400 nm.

[0055] (4) The catalyst precursor obtained in step (3) was placed in a muffle furnace for calcination. The calcination conditions were as follows: the temperature was increased to 400°C at a rate of 5°C / min, and the mixture was calcined at 400°C for 4 hours in an air atmosphere to obtain an unformed catalyst A1 (wherein the mass ratio of Cu:Zn:Al was 44.9:44.4:10.7). The scanning electron microscope image of the catalyst precursor was as follows: Figure 3 ,Depend on Figure 3 It can be seen that the catalyst is a microsphere structure with a particle size of 10 to 50 μm. The specific surface area of ​​the unformed catalyst A1 is 78.70 m 2 / g, pore volume is 0.51m 3 / g, and the average pore size is 26.02nm. 3% graphite is added to the catalyst powder, and the mixture is tableted and crushed, and the particles with a mesh size of 20-40 are sieved to obtain the molded catalyst A1.

[0056] The catalyst prepared by the present invention is used for dehydrogenation of 1,4-butanediol to produce γ-butyrolactone under normal pressure. The formed catalyst A1 is selected as the catalyst. The catalyst is reduced with hydrogen before the reaction. The reduction conditions are as follows: the hydrogen pressure is 0.1MPa, the reduction temperature is 270°C, and the reduction time is 12h. After the reduction is completed, the reaction is carried out under the following conditions: the reaction temperature is 220°C; the feed volume space velocity is 1.0h -1 ; H2 / alcohol molar ratio 5:1, after 500h of operation, 1,4-butanediol conversion rate is 99.8%; γ-butyrolactone selectivity is 98.2%.

[0057] Example 2

[0058] (1) copper nitrate, zinc nitrate and aluminum nitrate were prepared into a metal salt solution with a mass ratio of copper:zinc:aluminum of 45:45:10 and a concentration of 2.0 mol / L, and rapeseed pollen (particle size of 20 to 50 μm) was added thereto, and the concentration of the bio-template in the obtained mixture was controlled to be 0.1 g / mL;

[0059] (2) The precipitant solution is a sodium carbonate aqueous solution, and the concentration of the precipitant solution is 1.0 mol / L; the acid-base coprecipitation process is adopted, and the mixture obtained in step (1) and the precipitant solution are added in parallel, and the reaction temperature is controlled at 60°C, the reaction pH value is 7.0, and the reaction time is 2 hours. After the reaction is completed, it is aged at 70°C for 2 hours, filtered and separated, and washed with deionized water for 6 times, and dried in an oven at 60°C for 12 hours, and the catalyst precursor is collected. From the XRD diagram of the catalyst precursor, it can be seen that the precursor is a copper-zinc-aluminum hydrotalcite structure.

[0060] (3) The catalyst precursor obtained in step (2) was placed in a muffle furnace for calcination. The calcination conditions were as follows: the temperature was increased to 400°C at a rate of 6°C / min, and calcined at 400°C for 2h in an air atmosphere to obtain an unformed catalyst A2 (wherein the mass ratio of Cu:Zn:Al was 44.8:43.9:11.3). The scanning electron microscope image of the catalyst precursor was as follows: Figure 4 ,Depend on Figure 4 It can be seen that the catalyst is a microsphere structure with a particle size of 10 to 50 μm. The specific surface area of ​​the unformed catalyst A1 is 51.27 m 2 / g, pore volume is 0.31m 3 / g, and the average pore size was 26.77nm. 3% graphite was added to the catalyst powder, and the mixture was tableted and crushed, and 20-40 mesh particles were sieved to obtain a molded catalyst A2.

[0061] The catalytic reaction conditions were the same as those in Example 1. After 500 hours of operation, the reaction results were as follows: the conversion rate of 1,4-butanediol was 99.7%; and the selectivity of γ-butyrolactone was 98.0%.

[0062] Example 3

[0063] (1) copper nitrate, zinc nitrate and aluminum nitrate were prepared according to the mass ratio of copper: zinc: aluminum of 42.5:42.5:15, and the concentration of the metal salt solution was 2.0 mol / L, and lotus powder (particle size of 20-50 μm) was added thereto, and the concentration of the bio-template in the obtained mixture was controlled to be 0.1 g / mL;

[0064] (2) The precipitant solution is a sodium bicarbonate aqueous solution, and the concentration of the precipitant solution is 1.0 mol / L; an acid-base coprecipitation process is adopted, and the mixture obtained in step (1) and the precipitant solution are added in parallel, and the reaction temperature is controlled at 70°C, the reaction pH value is 7.5, and the reaction time is 2 hours. After the reaction is completed, it is aged at 75°C for 2 hours, filtered and separated, and washed with deionized water for 6 times, and dried in an oven at 60°C for 12 hours, and a catalyst precursor is collected. From the XRD diagram of the catalyst precursor, it can be seen that the precursor is a copper-zinc-aluminum hydrotalcite structure.

[0065] (3) The catalyst precursor obtained in step (2) was placed in a muffle furnace for calcination. The calcination conditions were as follows: the temperature was increased to 400°C at a rate of 7°C / min, and the mixture was calcined at 400°C for 4 hours in an air atmosphere to obtain an unformed catalyst A3 (wherein the mass ratio of Cu:Zn:Al was 42.7:41.2:16.1). The scanning electron microscope image of the catalyst precursor was as follows: Figure 5 ,Depend on Figure 5 It can be seen that the catalyst is a microsphere structure with a particle size of 10 to 50 μm. The specific surface area of ​​the unformed catalyst A3 is 83.51 m 2 / g, pore volume is 0.49m3 / g, and the average pore size was 23.43nm. The catalyst powder was added with 3% graphite, tableted, crushed, and sieved to obtain particles of 20-40 mesh to obtain a molded catalyst A3.

[0066] The catalytic reaction conditions were the same as those in Example 1. After 500 hours of operation, the reaction results were as follows: the conversion rate of 1,4-butanediol was 99.3%; and the selectivity of γ-butyrolactone was 98.2%.

[0067] Comparative Example 1

[0068] (1) copper nitrate, zinc nitrate and aluminum nitrate are used to prepare a metal salt solution with a mass ratio of copper:zinc:aluminum of 45:45:10 and a concentration of 2.0 mol / L;

[0069] (2) The precipitant solution is a sodium bicarbonate aqueous solution, and the concentration of the precipitant solution is 1.0 mol / L; the acid-base co-precipitation process is adopted, and the mixture obtained in step (1) and the precipitant solution are added in parallel, and the reaction temperature is controlled at 60°C, the reaction pH value is 7.0, and the reaction time is 2h. After the reaction is completed, it is aged at 70°C for 2h, filtered and separated, washed with deionized water for 6 times, and dried in an oven at 60°C for 12h to collect the catalyst precursor;

[0070] (3) The catalyst precursor obtained in step (2) was placed in a muffle furnace for calcination. The calcination conditions were as follows: the temperature was increased to 400°C at a rate of 5°C / min, and calcined at 400°C for 4 hours in an air atmosphere to obtain an unformed catalyst B1. The scanning electron microscope image of the catalyst is shown in FIG. Figure 6 ,Depend on Figure 6 It can be seen that the catalyst is an irregular particle aggregate structure with a particle size of 5 to 40 μm. The specific surface area of ​​the unformed catalyst B1 is 65.81 m 2 / g, pore volume is 0.41m 3 / g, and the average pore size is 24.71nm. The catalyst powder is added with 3% graphite, and is tableted and crushed, and the particles of 20-40 mesh are sieved to obtain the molded catalyst B1.

[0071] The catalytic reaction conditions were the same as those in Example 1. After 500 hours of operation, the reaction results were as follows: 1,4-butanediol conversion was 98.1%; and γ-butyrolactone selectivity was 97.1%.

[0072] Comparative Example 2

[0073] (1) copper nitrate, zinc nitrate and aluminum nitrate are prepared according to the molar ratio of copper:zinc:aluminum of 45:45:10 to prepare a metal salt solution with a concentration of 2.0 mol / L;

[0074] (2) The precipitant solution is a sodium bicarbonate aqueous solution, and the concentration of the precipitant solution is 1.0 mol / L; the acid-base co-precipitation process is adopted, and the mixture obtained in step (1) and the precipitant solution are added in parallel, and the reaction temperature is controlled at 60°C, the reaction pH value is 7.0, and the reaction time is 2 hours. After the reaction is completed, the same lotus powder as in Example 1 is added, aged at 70°C for 2 hours, filtered and separated, washed with deionized water for 6 times, dried in an oven at 60°C for 12 hours, and the catalyst precursor is collected;

[0075] (3) The catalyst precursor obtained in step (2) was placed in a muffle furnace for calcination. The calcination conditions were as follows: the calcination temperature was increased to 400°C at a rate of 5°C / min, and calcined at 400°C for 4 hours in an air atmosphere to obtain an unformed catalyst B2. The scanning electron microscope image of the catalyst is shown in FIG. Figure 7 ,Depend on Figure 7 It can be seen that the catalyst has an irregular particle structure with a particle size of 10 to 50 μm. The specific surface area of ​​the unformed catalyst B2 is 50.30 m 2 / g, pore volume is 0.13m 3 / g, and the average pore size is 10.46nm. The catalyst powder is added with 3% graphite, and is tableted and crushed, and the particles of 20-40 mesh are sieved to obtain the molded catalyst B2.

[0076] The catalytic reaction conditions were the same as those in Example 1. After 500 hours of operation, the reaction results were as follows: the conversion rate of 1,4-butanediol was 97.4%; and the selectivity of γ-butyrolactone was 96.7%.

[0077] Comparative Example 3

[0078] (1) copper nitrate, zinc nitrate and aluminum nitrate were prepared into a metal salt solution with a mass ratio of copper:zinc:aluminum of 45:45:10 and a concentration of 2.0 mol / L, and rapeseed pollen (particle size of 20 to 50 μm) was added thereto, and the concentration of the bio-template in the obtained mixture was controlled to be 0.1 g / mL;

[0079] (2) The precipitant solution is a sodium carbonate aqueous solution, and the concentration of the precipitant solution is 1.0 mol / L; the acid-base co-precipitation process is adopted, and the mixture obtained in step (1) and the precipitant solution are added in parallel, and the reaction temperature is controlled at 60°C, the reaction pH value is 7.0, and the reaction time is 2h. After the reaction is completed, it is aged at 70°C for 2h, filtered and separated, washed with deionized water for 6 times, and dried in an oven at 60°C for 12h to collect the catalyst precursor;

[0080] (3) The catalyst precursor obtained in step (2) was placed in a muffle furnace for calcination. The calcination conditions were as follows: the calcination temperature was increased from 2°C / min to 400°C, and calcined at 400°C for 2h in an air atmosphere to obtain an unformed catalyst B3. The scanning electron microscope image showed that the catalyst was an irregular aggregate structure with a particle size of 10 to 50 μm. The specific surface area of ​​the unformed catalyst B3 was 39.57 m 2 / g, pore volume is 0.22m 3 / g, and the average pore size was 21.92nm. 3% graphite was added to the catalyst powder, and the mixture was tableted and crushed, and then 20-40 mesh particles were sieved to obtain a molded catalyst B3.

[0081] The catalytic reaction conditions were the same as those in Example 1. After 500 hours of operation, the reaction results were as follows: the conversion rate of 1,4-butanediol was 98.2%; and the selectivity of γ-butyrolactone was 96.9%.

Claims

1. A 1,4-butanediol dehydrogenation catalyst precursor, comprising a biological template and Cu / Zn / Al hydrotalcite.

2. The precursor according to claim 1, characterized in that The precursor is a microsphere structure; and / or the particle size of the precursor is 20 to 50 μm.

3. The precursor according to claim 1, characterized in that The biological template is selected from one or more of lotus pollen, sunflower pollen, rapeseed pollen, lotus pollen and camellia pollen.

4. The precursor according to claim 1, characterized in that In the precursor, Cu / Zn / Al hydrotalcite particles are evenly distributed on the surface of the biological template, and the particle size is 50-500nm.

5. The precursor according to claim 1, characterized in that In the precursor, the mass ratio of Cu / Zn / Al of the Cu / Zn / Al hydrotalcite is (30-60):(30-60):(5-40).

6. The method for synthesizing the precursor according to any one of claims 1 to 5, comprising: (1) preparing copper salt, zinc salt and aluminum salt solutions, and then mixing them with the biological template, wherein the concentration of the biological template in the obtained mixture is controlled to be 0.01 to 0.5 g / mL; (2) Acid-base co-precipitation process is adopted to add the mixture obtained in step (1) and the precipitant solution in parallel, and after the reaction is completed, the mixture is aged, filtered, washed and dried to obtain a catalyst precursor.

7. The synthesis method according to claim 6, characterized in that In step (1), the copper salt, zinc salt and aluminum salt are soluble metal salts, preferably at least one of nitrate, sulfate and acetate; the solvent used in the metal salt solution is at least one of water, methanol, ethanol and N,N-dimethylformamide; further preferably, in the copper salt, zinc salt and aluminum salt solution, the total concentration of copper, zinc and aluminum ions is 0.5 to 5.0 mol / L.

8. The synthesis method according to claim 6, characterized in that In step (1), the biological template is selected from one or more of lotus pollen, sunflower pollen, rapeseed pollen, lotus pollen, and camellia pollen; and the particle size of the biological template is 20 to 50 μm.

9. The synthesis method according to claim 6, characterized in that: In step (1), the molar ratio of the copper salt calculated as copper, the zinc salt calculated as zinc, and the aluminum salt calculated as aluminum is (0.5-2.0):(0.5-2.0):(0.1-1.0).

10. The synthesis method according to claim 6, characterized in that: The precipitant used in the precipitant solution in step (2) is selected from one or more of sodium carbonate, sodium hydroxide, sodium bicarbonate and ammonia water; the concentration of the precipitant solution is 0.5-5.0 mol / L; the solvent used in the precipitant solution is selected from one or more of methanol, ethanol, water and N,N-dimethylformamide.

11. The synthesis method according to claim 6, characterized in that: In step (2), the reaction conditions are: reacting at 25-80°C for 0.5-5h, and controlling the reaction pH value to be 6.0-9.0; and / or, the aging conditions are as follows: aging temperature is 25-80°C, aging time is 0.5-5h, and pH value is 6.0-9.

0.

12. The synthesis method according to claim 6, characterized in that: The drying conditions are as follows: drying temperature is 25-80°C, and drying time is 6-24h.

13. A 1,4-butanediol dehydrogenation catalyst, characterized in that: The product is obtained by calcining the precursor according to any one of claims 1 to 5 or the precursor obtained by the method according to any one of claims 6 to 12.

14. The catalyst according to claim 13, characterized in that The specific surface area of ​​the catalyst is 40 to 150 m 2 / g, pore volume is 0.20~0.65m 3 / g, and the average pore size is 20-28nm.

15. The catalyst according to claim 13, characterized in that The calcination conditions are as follows: the heating rate to the calcination temperature is 4-8°C / min, the calcination temperature is 300-500°C, the calcination time is 2-6h, and the calcination atmosphere is an oxygen-containing atmosphere.

16. A method for preparing a 1,4-butanediol dehydrogenation catalyst, comprising: The catalyst is obtained by calcining the precursor according to any one of claims 1 to 5 or the precursor obtained by the method according to any one of claims 6 to 12.

17. The preparation method according to claim 16, characterized in that: The calcination conditions are as follows: the heating rate to the calcination temperature is 4-8°C / min, the calcination temperature is 300-500°C, the calcination time is 2-6h, and the calcination atmosphere is an oxygen-containing atmosphere.

18. Use of the catalyst according to any one of claims 11 to 15 or the catalyst obtained by the method according to any one of claims 16 to 17 in the dehydrogenation of 1,4-butanediol to synthesize γ-butyrolactone.

19. The use according to claim 18, characterized in that The reaction conditions are as follows: reaction temperature is 150-300°C, preferably 215-230°C, reaction pressure is 0.1-1.0 MPa, preferably 0.1-0.5 MPa, volume space velocity is 0.1-2.0 h -1 , preferably 0.3 to 1.5h -1 The molar ratio of hydrogen to 1,4-butanediol is 1 to 150:1, preferably 1 to 30:1.

Citation Information

Patent Citations

  • Production method of gamma-butyrolactone

    CN103044367B

  • Catalyst for preparing gamma-butyrolactone by normal-pressure gas-phase dehydrogenation of 1,4-butanediol and preparation method thereof

    CN103877981B

  • A catalyst for the dehydrogenation of 1,4-butanediol to prepare γ-butyrolactone and its preparation method.

    CN110773174B

Cited By

  • Catalyst for circulating hydrogen storage of 1, 4-butanediol / gamma-butyrolactone as well as preparation method and application of catalyst

    CN121551023A